The Use of Digital Media in Improving Students' Understanding of Fiqh Material at MIS Hidayatut Thowalib - Muthoisyah; Muhyidin (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2025)
This study aims to analyze the use of digital media in enhancing students' understanding of Fiqh subjects at MIS Hidayatut Thowalib. In the digital era, integrating technology into education has become increasingly essential to improve the effectiveness of the teaching and learning process. This research employs a qualitative approach with a descriptive method. Data were collected through observations, interviews, and documentation involving teachers and students who participated in Fiqh lessons using digital media. The findings indicate that the use of digital media, such as educational videos, interactive presentations, and learning applications, significantly enhances students' comprehension of Fiqh concepts. The visual appeal and interactivity of digital media make it easier for students to grasp abstract concepts in Fiqh. Moreover, students become more motivated to learn and actively engage in classroom discussions. However, challenges such as limited internet access and teachers’ lack of technological proficiency hinder the optimal use of digital media in learning. Overall, this study demonstrates that digital media positively impact students' understanding of Fiqh lessons. Therefore, teacher training in integrating technology into teaching and improved supporting facilities are necessary to maximize the benefits of digital media in education.